Teachers’ Inclusion of Students with Sensory Disability in Nigerian Classrooms: A Review - Ekpete, Obutor Happiness; Blessing, Legborsi Grace (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study reviews the inclusion of students with sensory disability in Nigerian classrooms. It examines the challenges, strategies, and practical realities faced by educators in implementing inclusive education for learners with visual and hearing impairments. Despite supportive policies like Nigeria's National Policy on Education (2014) and international frameworks, the integration of students with sensory disability into regular classrooms remains limited due to factors such as inadequate infrastructure, insufficient teacher training, societal attitudes, and lack of appropriate teaching resources. The review highlights the importance of inclusive curriculum design, multi-sensory instructional approaches, differentiated assessments, and assistive technologies in enhancing the learning experiences of students with sensory impairments. The paper concludes by recommending stronger policy enforcement, targeted teacher training, provision of learning resources, and increased societal awareness. By focusing on teachers’ roles and challenges, this review contributes to the ongoing discourse on inclusive education in Nigeria and provides practical insights for policy and practice.